Analisis Bisnis Rokok Tradisional dalam Novel Gadis Kretek Karya Ratih Kumala - Davina Catharine Utami; Farah Diva Amelia; Eva Dwi Kurniawan (AKUA: Jurnal Akuntansi dan Keuangan, 2024)
Analyzing and understanding the traditional cigarette business in the novel Girl Kretek by Ratih Kumala as a representation of the traditional cigarette business in Indonesian society is the aim of this research. The method used in this research is qualitative method. The data source for this research is the novel Kretek Girl by Ratih Kumala. The research results show that utilizing situations to make things profitable for oneself is a spirit that every business person must have. Based on the results of the analysis and discussion that has been carried out, the researcher can conclude that the novel Kretek Girl by Ratih Kumala provides a strong picture of how valuable and strong the cultural heritage of the traditional cigarette business is in Indonesia. This business is not just an economic activity, but also an integral part of society's culture and identity. In this novel, we also see that the traditional cigarette business is not always easy. There are various challenges faced by business people, including competition with the large cigarette industry, cultural changes, and economic factors.